-4(6y-9)-y=-2(y-3)

Simple and best practice solution for -4(6y-9)-y=-2(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6y-9)-y=-2(y-3) equation:


Simplifying
-4(6y + -9) + -1y = -2(y + -3)

Reorder the terms:
-4(-9 + 6y) + -1y = -2(y + -3)
(-9 * -4 + 6y * -4) + -1y = -2(y + -3)
(36 + -24y) + -1y = -2(y + -3)

Combine like terms: -24y + -1y = -25y
36 + -25y = -2(y + -3)

Reorder the terms:
36 + -25y = -2(-3 + y)
36 + -25y = (-3 * -2 + y * -2)
36 + -25y = (6 + -2y)

Solving
36 + -25y = 6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
36 + -25y + 2y = 6 + -2y + 2y

Combine like terms: -25y + 2y = -23y
36 + -23y = 6 + -2y + 2y

Combine like terms: -2y + 2y = 0
36 + -23y = 6 + 0
36 + -23y = 6

Add '-36' to each side of the equation.
36 + -36 + -23y = 6 + -36

Combine like terms: 36 + -36 = 0
0 + -23y = 6 + -36
-23y = 6 + -36

Combine like terms: 6 + -36 = -30
-23y = -30

Divide each side by '-23'.
y = 1.304347826

Simplifying
y = 1.304347826

See similar equations:

| 3+2n-1=7n+4-4n | | 2u-(8)+3v= | | 2x-4+0.5x+0.2(2x-4+8)=26 | | (2x+7)6=-7x+4 | | 2u-8+3v= | | 8(x+7.4)-8x+12= | | 37x+8=6(6x+1) | | -6+g=11 | | 37+w=5w-35 | | 5x-8x+3=x-6+9 | | 5x-3(2x-1)=8x-1 | | .04(x+10)+.6x=29 | | 3x+7-5(x+1)=5x+8 | | 10(6)+10-6(-7-6)= | | x^5=7 | | 400x+3858=6374 | | n+n+2=206 | | n+n+1+n+2=111 | | n+n+1=5 | | -5x-5=40 | | x^2+8=8x-8 | | 2r^2+10r+12=0 | | 3(2x-1.3)=2(3x-2.1)-3(x-0.7) | | .5(x+50)+.3x=41 | | (7n+4)= | | -2x=-3y+10 | | 4(8+2x)=5x+11 | | (7n+4)(n+5)= | | 9x-3x-2=0 | | 450.00-35.00= | | (3x-1)(4x-3)= | | x+7=x-2 |

Equations solver categories